1990
DOI: 10.1007/bf01342754
|View full text |Cite
|
Sign up to set email alerts
|

Parent and peer attachment in early adolescent depression

Abstract: Insecure attachment relations have been theorized to play a significant role in the development of depressogenic modes of adaptation and to thus form a vulnerability factor for the emergence of depressive disorder in children. This study examined security of parent and peer attachment among four groups of early adolescents: clinically depressed, nondepressed psychiatric controls, nonpsychiatric controls, and adolescents with resolved depression. Depressed adolescents reported significantly less secure parent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
171
1
12

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(203 citation statements)
references
References 23 publications
19
171
1
12
Order By: Relevance
“…In this interactional approach, excessive reassuranceseeking is coupled with rejection by others, resulting in an increasingly negative interpersonal experience, increased reassurance-seeking, and an unpleasant ongoing cycle and greater depression. A clear model with data to support an interactional model of depression remains unavailable (Coyne, 1999), but several studies have noted links between perceptions of parental perceptions and emotional availability, theoretically related to attachment, and depression (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990;Burge et al, 1997;Cole-Detke & Kobak, 1996;. In a recently published article, Abela et al (2005) reported that severity of depressive symptoms was related to perceptions of parenting that are consistent with insecure attachment, but the relationship was moderated by the youth's excessive reassurance seeking.…”
Section: Attachment-asmentioning
confidence: 99%
“…In this interactional approach, excessive reassuranceseeking is coupled with rejection by others, resulting in an increasingly negative interpersonal experience, increased reassurance-seeking, and an unpleasant ongoing cycle and greater depression. A clear model with data to support an interactional model of depression remains unavailable (Coyne, 1999), but several studies have noted links between perceptions of parental perceptions and emotional availability, theoretically related to attachment, and depression (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990;Burge et al, 1997;Cole-Detke & Kobak, 1996;. In a recently published article, Abela et al (2005) reported that severity of depressive symptoms was related to perceptions of parenting that are consistent with insecure attachment, but the relationship was moderated by the youth's excessive reassurance seeking.…”
Section: Attachment-asmentioning
confidence: 99%
“…Further support for the importance of caregiver relationships in adolescent depression and suicide can be found in the broader literature bases on interpersonal trust and attachment security. For example, higher interpersonal trust has been associated with reduced internalizing symptoms in adolescents (Rotenberg, Sharp, & Venta, under review), and secure attachment relationships with caregivers have been linked with reduced depression (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990) and suicidality (de Jong, 1992) among adolescents. Moreover, adolescents with psychiatric symptoms who perceive their caregivers as unavailable engage in more suicidal behaviors (West, Spreng, Rose, & Adam, 1999).…”
mentioning
confidence: 99%
“…It is important to examine both kinds of relationships, as adolescence is characterized by a process of individuation from the family (Furman & Buhrmester, 1992), and both parent and peer attachments are associated with adolescent depression (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990). Specifically, we consider factors related to the quality of adolescents' relationships with parents (e.g., parental depression, parenting practices) as well as their cognitions about peer relationships.…”
mentioning
confidence: 99%